PERANCANGAN WEBSTORAGE MENGGUNAKAN FREENAS 8 BERBASIS PRIVATE CLOUD: Studi Kasus Fakultas Ilmu Komputer Universitas Methodist Indonesia - Raje Veer; Fati Gratianus Nafiri Larosa (Universitas Methodist Indonesia, 2017)
The user of tablet, laptop dan computer which browse the internet, storing the data using a big hard drive on the laptop and computer, others choose to erase the old data to make more space for storing the new data. WebStorage with Private Cloud based is the storage media for storing the data on the existing virtual server. Using WebStorage become one of the alternatives for storing the data beside hard drive, CD/DVD or another hardware. The data manage with the database on the virtual server. The storage allocated by FreeNAS and attached to Linux Mint as virtual server through iSCSI protocol. Accessing it by client only need a internet/intranet connection. FreeNAS and Linux Mint are Open Source Operating System, and they are download freely. This WebStorage System developed using PHP and MySQL, and located on Virtual Server at The Laboratory of Fakultas Ilmu Komputer, Universitas Methodist Indonesia Medan (UMI Medan). This WebStorage gives storage services for Lecturers, Staffs and Students with by using registered account